Utilizing online serious games to facilitate distributed requirements elicitation - Ghanbari, Hadi; Similä, Jouni; Markkula, Jouni (The Journal of systems and software, 2015)
•Online serious games are used to facilitate distributed requirements elicitation.•Interactive games enhance collaboration and communication between project members.•Serious games raise individuals’ confidence to engage in requirements elicitation.•Using serious games can improve both quality and quantity of software requirements.•Serious games specially enhance the performance of less-experienced stakeholders. Requirements elicitation is one of the most important and challenging activities in software development projects. A variety of challenges related to requirements elicitation are reported in the literature, of which the lack of proper communication and knowledge transfer between software stakeholders are among the most important. Communication and knowledge transfer are becoming even bigger challenges with the current increase in globally distributed software development projects due to the temporal, geographic, and sociocultural diversity among software stakeholders. In this study, we propose a new approach to requirements elicitation, which employs online serious games for gathering requirements from distributed software stakeholders. The feasibility and effectiveness of the proposed approach were evaluated in an empirical study with encouraging results. These results especially reveal that our suggested approach enables less-experienced individuals to identify a higher number of requirements. Our results also reveal that for the majority of subjects, especially individuals with less technical experience, this approach was a pleasant and easy way of participating in requirements elicitation. Based on these results we suggest that using online serious games not only enhances innovation and creativity among end-users but also facilitates collaboration and communication among software stakeholders. Implications for both research and practice are considered.